Decomposing monthly declines in subsurface-water pH and aragonite saturation state from spring to autumn in the North Yellow Sea. (1st September 2019) - Li, Cheng-long; Zhai, Wei-dong
Abstract: The North Yellow Sea (NYS) is a western North Pacific marginal sea of major ecological and economic importance, where seasonal thermocline and subsurface cold water mass are well developed from spring to autumn. Earlier researchers have shown monthly/bimonthly declines of pH (ΔpH) and aragonite saturation state (ΔΩarag ) in the NYS cold water mass. To quantify the biogeochemical processes controlling these variations, we applied a systematic decomposition methodology to ΔΩarag and ΔpH values, using the Redfield ratio and published data sets of NYS carbonate and ancillary parameters for 2011 and 2013. Results show that the contributions of the NYS cold water mass community respiration (ΔΩ Resp ), calcification (ΔΩ Calc ) and temperature changes (ΔΩ ΔT ) to the monthly ΔΩarag from spring to summer were 84 ± 9%, 30 ± 16%, and − 13 ± 10%, while the ΔΩ Resp, ΔΩ ΔT and contributions of CaCO3 dissolution (ΔΩ Diss ) to the bimonthly ΔΩarag from late summer to autumn were 103%, 1% and − 5%. Meanwhile, the contributions of the NYS cold water mass community respiration (ΔpH Resp ), temperature changes (ΔpH ΔT ) and calcification (ΔpH Calc ) to the monthly ΔpH from spring to summer were 50 ± 23%, 39 ± 23%, and 13 ± 4%, while the ΔpH Resp, ΔpH ΔT and contributions of CaCO3 dissolution (ΔpH Diss ) to the bimonthly ΔpH from late summer to autumn were 110%, − 5%, and − 5%. Our results suggest that the NYS cold water mass net calcification rate declines to nearly zero when Ωarag reaches a critical level of 1.5 − 1.6. Using a future scenario to predict the impacts of rising atmospheric CO2 levels on seasonal variations of Ωarag and pH values, we show that very low Ωarag values of < 1.5 may exist all year round in the NYS subsurface waters by the 2050 s, while aragonite undersaturated water (Ωarag <1) may appear in autumn months, causing great stress to its benthic faunal community. Highlights: Controlling processes of the North Yellow Sea (NYS) seasonal acidification were quantified. Net calcification rate declines to zero when seawater aragonite saturation state reaches 1.5–1.6. Calcification-unfavorable waters may exist in NYS subsurface layers all year round in the 2050 s.